Perlakuan Pajak Pertambahan Nilai Transaksi E-Commerce Di Indonesia - Setiadi Alim Lim; Lilik Indrawati (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2016)
Developments in science and technology is very rapid at the end of the 20th century, especially information and communication technologies have caused changes in many areas of life, including the business life. One of the benefits of information and communication technologies in the business world is the support of the implementation of bisnis transactions are done online or so-called ecommerce (electronic commerce) through the use of the internet network. Ecommerce transactions are growing very rapidly from year to year. Given the potential tax revenue from this sector, governments around the world must give great attention to the taxation of e-commerce transactions, including the imposition of Value Added Tax. In Indonesia, the taxation of e-commerce transactions are regulated in Circular of the Director General of Tax No. SE-62/PJ/2013 dated December 27, 2013. But what is regulated in Circular of the Director General of Tax No. SE-62/PJ/2013 dated December 27, 2013 is deemed still not enough to regulate all matters relating to the imposition of Value Added Tax on e-commerce transactions. Therefore, it is necessary to develop a set of rules comprehensive for the imposition of Value Added Tax on e-commerce transactions.